Prevalência dos sintomas do transtorno de déficit de atenção e hiperatividade em crianças de 1ª a 3ª série de escolas de Belém – Pa - BARBOSA, Bruna Nayana Ribeiro (2023)
The attention deficit and hyperactivity disorder (ADHD) has higher prevalence among students. This article aims analyzing the prevalence of symptoms of ADHD among students ranging between the 1st and the 3rd grade of public and private schools in the City of Belém PA, as well as comparing this prevalence among the schools, between the genders and what subtype is the most revealed. The participant schools were chosen randomly, being the sample composed by 313 students from private schools and by 368 from public schools. A questionnaire called SNAP – IV was applied to the teachers of those students. The result of this questionnaire classifies children as having more symptoms than the expected for hyperactivity/impulsiveness, for attention deficit or for a combination of those symptoms. The results showed that the prevalence of the ADHD symptoms reached 23.9% within the sample; the students from public schools presented more symptoms than those from private schools (30.4% against 16.3%, respectively); the male gender was the most affected by the symptoms (71%); and attention deficit was the most prevalent subtype (47%). The results collected in the present study are similar to those presented in previous articles, highlighting the necessity of further future researches among the students of Belém-PA due to the registered high prevalence.